Labouring in the Sex Industry: A Conversation with Sex Workers on Consent and Exploitation - Tremblay, Francine (Social sciences (Basel), 2021)
Sex work in all its forms is an occupation that belongs to the service industry, and like any other work, sexual labour is open to exploitation. However, the reason why sex work is seen to be different from other forms of labour is that it betrays the socially accepted rules of love and intimacy and is exercised within a criminalised environment. As a cultural symbol, sex work remains steadfastly linked to aberration and dangerousness. This article juxtaposes the legal and lay definitions of consent and exploitation based on conversations with fourteen Canadian sex workers. The objective of this exploratory article is to delve within two ill-defined and highly contested notions related to the sex industry—consent and exploitation.